2022
DOI: 10.3390/nano12224075
|View full text |Cite
|
Sign up to set email alerts
|

On the Application of Calcium Phosphate Micro- and Nanoparticles as Food Additive

Abstract: The human body needs calcium and phosphate as essential nutrients to grow bones and teeth, but they are also necessary for many other biochemical purposes (e.g., the biosynthesis of phospholipids, adenosine triphosphate, ATP, or DNA). The use of solid calcium phosphate in particle form as a food additive is reviewed and discussed in terms of bioavailability and its safety after ingestion. The fact that all calcium phosphates, such as hydroxyapatite and tricalcium phosphate, are soluble in the acidic environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Enax et al [ 72 ] reviewed the safety of calcium phosphates, including biomimetic HAP, and it was concluded that HAP can be safely swallowed when used in oral care products. However, most subjects expectorate and rinse after using their toothpaste.…”
Section: Discussionmentioning
confidence: 99%
“…Enax et al [ 72 ] reviewed the safety of calcium phosphates, including biomimetic HAP, and it was concluded that HAP can be safely swallowed when used in oral care products. However, most subjects expectorate and rinse after using their toothpaste.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium phosphates, in general, can be incorporated into various oral care products such as toothpaste [ 25 , 26 , 58 ], mouthwashes [ 31 , 32 ], and oral gels [ 59 ]. A clear advantage of calcium phosphates is their biomimetic characteristic [ 40 ]. Consequently, higher effective doses can be used with no risk of toxicity (unlike fluoride) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, calcium phosphates (e.g., hydroxyapatite) have been shown to be beneficial for pain relief of MIH-associated tooth sensitivity [ 18 , 20 , 36 ]. Unlike fluorides which can cause dental fluorosis and other side effects [ 37 , 38 , 39 ], calcium phosphates show excellent biocompatibility and are safe if swallowed [ 40 ]. Note that nanoparticular amorphous calcium phosphate is present, e.g., in human breast milk [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a globally used biomimetic ingredient in oral care products is particulate hydroxyapatite, Ca 5 (PO 4 ) 3 (OH), a synthetic calcium phosphate mineral that is inspired by the natural enamel crystallites [ 10 , 11 ]. Hydroxyapatite shows good biocompatibility when used in oral care products, and it is also used as a food additive [ 12 , 13 ]. Various studies have shown its efficacy in different areas, such as caries prevention and the reduction of dentin hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%